Breaking new ground: New Zealand Certificates of Steiner Education - Boland, Neil; Brice-Geard, Karen; Bell, Amanda; Cook, Christine (Frontiers in Education, 2024)
The New Zealand Certificates of Steiner Education (CSE) are secondary qualifications at levels 1, 2 and 3, recognized by the New Zealand Qualifications Authority. They give access to tertiary education in New Zealand and beyond. The impulse for new qualifications grew from a wish to have important aspects of the taught Steiner curriculum recognized and valorized, that these aspects be credit bearing towards tertiary study, an option not offered by existing qualifications. The certificates were developed over an 18-month period and were implemented by the (then) four New Zealand Steiner schools with high school classes. The CSE are based on a suite of learning outcomes which give teachers a substantial degree of assessment autonomy, allowing them to tailor assessment modalities to the student or class being taught. Since 2012, the qualifications have been offered overseas and are now used as a pathway to university by Steiner schools in a growing number of countries. This article draws on the experiences of one of the developers of the qualification and two teachers in schools using the certificate in the UK, and outlines some of the challenges faced when breaking new ground in the advancement of Waldorf education internationally.